2016
DOI: 10.1002/jsfa.7778
|View full text |Cite
|
Sign up to set email alerts
|

The impact of canopy managements on grape and wine composition of cv. ‘Istrian Malvasia’ (Vitis vinifera L.)

Abstract: Leaf removal at véraison and Double Maturation Raisonnée improved the phenolic composition of wine, producing a full-bodied wine. On the other hand, early leaf removal significantly augmented the yield and titratable acidity, hydroxycinnamic acids and flavanols of wine, which might have led to a fresher but less-bodied wine. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Rusjan and Mikulic‐Petkovsek observed that Merlot berries from cane‐cut vines reached significantly higher soluble acid levels and titratable acidity values in comparison to control berries at harvest. Other studies performed on Refosk, Istrian Malvasia, and Rebula grape berries exhibited a significant increase in titratable acidity, tartaric acid, and malic acid when the cane‐cut on‐vine technique was applied to the vineyard compared to the control. This behavior was affected by the season in Istrian Malvasia.…”
Section: Resultsmentioning
confidence: 89%
“…Rusjan and Mikulic‐Petkovsek observed that Merlot berries from cane‐cut vines reached significantly higher soluble acid levels and titratable acidity values in comparison to control berries at harvest. Other studies performed on Refosk, Istrian Malvasia, and Rebula grape berries exhibited a significant increase in titratable acidity, tartaric acid, and malic acid when the cane‐cut on‐vine technique was applied to the vineyard compared to the control. This behavior was affected by the season in Istrian Malvasia.…”
Section: Resultsmentioning
confidence: 89%
“…In recent studies on the Raboso Piave variety, DMR significantly increased the content of soluble solids and total phenolics in grapes, but decreased total acidity and the content of malic acid, whereas grape pH remained unaffected and resulted in brighter coloured and less astringent wines . Moreover, DMR stimulated the synthesis of flavonols and stilbenoids but reduced the contents of flavanols, especially procyanidins B1 and B2 in grapes and wines of Raboso Piave, which was partly confirmed in Malvasia grape and wine …”
Section: Introductionmentioning
confidence: 74%
“…Ten panellists (trained and long‐term experienced wine tasters) evaluated the wine following the score ranking (out of a maximum 30 points): clearness maximum 2 points, colour maximum 2 points, odour maximum 4 points, taste maximum 6 points, harmony maximum 6 points, astringency maximum 5 points and bitterness maximum 5 points. The aim of the sensory evaluation was the possible impact of DMR on wine sensorial characteristics, especially on astringency and bitterness on the basis of previous reports …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations